Associations of breastfeeding duration with serum lipid values from infancy until age 20 years - the STRIP study - Laitinen, Tomi T. (SAGE PUBLICATIONS LTD, 2025)
Background and aims: The effect of breastfeeding duration on childhood lipid levels has remained controversial. In this study, we aimed to establish the long-term associations of breastfeeding duration with future levels of total cholesterol, high-density lipoprotein (HDL) cholesterol, non-HDL cholesterol and low-density lipoprotein cholesterol. In addition, we report lipid levels at the age of seven months depending on the child receiving any breastmilk.
Methods: The sample comprised 999 children participating in the prospective Special Turku Coronary Risk Factor Intervention Project (STRIP). Serum lipid profile was studied at the ages of seven months and 13 months, and annually thereafter until the age of 20 years. Duration of breastfeeding was inquired, and infants were divided into those who received or did not receive any breast milk at the age of seven months (n=533 and n=466, respectively). In addition, breastfeeding duration groups (any breastfeeding for 0-4 months, 4-6 months, 6-9 months, and >9 months) were formed.
Results: At the age of seven months infants who at that time received breast milk had higher serum HDL cholesterol (0.95±0.21mmol/l vs. 0.90±0.19 mmol/l; p=0.0018), non-HDL cholesterol (3.38±0.78 mmol/l vs. 3.01±0.67 mmol/l; p<0.001) and total cholesterol levels (4.33±0.80 mmol/l vs. 3.91±0.69 mmol/l; p<0.001) than their peers who did not receive breast milk. From two to 20 years of age serum lipid levels showed no consistent differences between the breastfeeding duration groups.
Conclusions: Our long-term data showed that duration of breastfeeding has no consistent associations with serum lipid concentrations in healthy individuals aged two to 20 years.